(3GdSehe djGQjhbGs - (3CHh HcQ CMeO Hf Ydj Hf GdeNJGQ Hf YHO GdcQje Hf LQKjG , GHf hMTjIs; (3jGQjhbGs ((3WQGHdS s)
(3ChdgG (B:s
(3CNS ef GdfHW , hCRd ef fHW hadGf jOYi Cfg YQHi hgh CNS ef fHWi , dG NjQ ajg s
(3BNQgG (B:s
(3hjTO Ydi ehVY dOZgG (B((3Ci YbQH(B) (3ajNQL GdSe Edi NGQLgG ajScf GdhLY , hdgG COhjI cKjQI , dcf gPg CHdZ hCLhO , hGdSdGe s
(3GfXQ agQS GdWH HQbe (B131 " (3cJGH GdSehe (B"s
(3fSNI fajSIs
(3jdjgG hQbJGf ai COhjI GdSehes
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdWHs